PERAN PARA PIHAK DALAM PENGELOLAAN KAWASAN KONSERVASI PENYU PANGUMBAHAN - Sambas Basuni; Burhanuddin Masy'ud; Fredinan Yulianda (Jurnal Analisis Kebijakan Kehutanan, 2014)
Sea turtle conservation policy focuses on setting some sea turtle nesting habitat as  conservation area. Pangumbahan sea turtle conservation area is one of the sea turtle conservation areas in Java island. The highest level of threat faced by sea turtle conservation requires an integrated multistakeholders roles. Therefore, the sea turtle conservation activities need an analysis to determine interests, importance, influence, and relations of various stakeholders in management of sea turtle conservation. This study aims at identifying, categorizing and investigating relationship among stakeholders, as well as formulating strategies to increase the role of stakeholders. Respondents were selected by snowball sampling method. In general, stakeholders are more involved in the utilization activities, which comprise 17 stakeholders, whereas the lowest stakeholders engagement are in preservation activities that comprise 8 stakeholders. Protection activities involved 14 stakeholders. Stakeholder relationships consist of conflict and communication. To meet the sea turtle conservation management objectives, the involvement of stakeholders needs to be improved through community empowerment, improvement and enhancement of collaborative community participation.